THE TRUTH ABOUT BILL GATES. - KRISS, SAM (First Things: A Monthly Journal of Religion & Public Life, 2022)
The author reflects on facts about billionaire Bill Gates. Topics discussed include the quality of life of billionaires based on people's imagination, the charitable works of Gates, the growth in the value of assets of the Gates Foundation Trust, and Gates' response to an interview about what had driven him to become the richest man in the world.